Preparation method of soybean protein fiber / sodium alginate double network embedded anthocyanin intelligent gel beads
Patent Information
- Application Number
- CN202611176230.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
然而,花青素在实际应用中面临两大技术瓶颈:一是其化学结构中含有多个酚羟基,对光、热、氧高度敏感,极易发生降解,导致指示性能衰减;二是其水溶性较强,在潮湿食品包装环境中易发生迁移和流失,影响指示的准确性和持久性
[0012](1) 本发明利用大豆蛋白纤维的交叉β-折叠结构内部疏水区域作为花青素的包埋位点,将矢车菊素-3-葡萄糖苷分子包埋于其中。该包埋效应从分子尺度上隔绝了光、热、氧对花青素的攻击,显著抑制了花青素的降解反应。与现有技术中花青素简单分散于凝胶基质中不同,本发明通过大豆蛋白纤维网络实现了对花青素的空间包埋和疏水稳定双重保护。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of intelligent food packaging and freshness detection technology, specifically relating to the preparation method and application of anthocyanin-encapsulated intelligent gel beads made from soybean protein fiber / sodium alginate dual network. Background Technology
[0002] Food safety is a critical issue concerning the national economy and people's livelihood. In the food supply chain, fresh foods such as meat and seafood are highly susceptible to spoilage due to microbial contamination and enzymatic hydrolysis during storage, transportation, and sales, causing not only huge economic losses but also seriously threatening consumer health. Therefore, developing intelligent packaging materials that can reflect food freshness in real time and intuitively has become a research hotspot in the field of food science. Anthocyanins are a class of natural water-soluble pigments, with cyanidin-3-glucoside (C3G) as their main component. They are widely found in plants such as red cabbage and mulberries, exhibiting good biocompatibility and antioxidant activity. Their structure changes under different pH conditions, resulting in a color change from red (pH<3) to purple (pH 5-6) and then to blue (pH>8), making them ideal pH-responsive indicators. However, anthocyanins face two major technical bottlenecks in practical applications: First, their chemical structure contains multiple phenolic hydroxyl groups, which are highly sensitive to light, heat, and oxygen, and are easily degraded, leading to a decline in indicator performance; second, they are highly water-soluble and are prone to migration and loss in humid food packaging environments, affecting the accuracy and durability of the indicator. Summary of the Invention
[0003] To address the problems faced by existing anthocyanins in practical applications, this invention provides a smart gel bead containing anthocyanins encapsulated in a soybean protein fiber / sodium alginate dual network and its preparation method.
[0004] This invention utilizes a dual-network interpenetrating structure formed by a soybean protein fiber network and a sodium alginate network to embed anthocyanin molecules (mainly cyanidin-3-glucoside) within the hydrophobic region of soybean protein fiber, and uses a sodium alginate gel framework for synergistic fixation, thereby achieving efficient stabilization of anthocyanins and synergistic enhancement of pH response sensitivity.
[0005] Soybean protein fiber is typically prepared under strongly acidic conditions (pH 2.0), where the fiber surface carries a large number of positive charges. When the acidic fiber dispersion is mixed with sodium alginate (an anionic polysaccharide with negatively charged carboxylate ions), the two will undergo instantaneous flocculation due to electrostatic attraction, forming an insoluble complex aggregate that cannot form a homogeneous composite system or be formed through calcium ion crosslinking. Therefore, the fiber dispersion must be adjusted to neutral before compounding to change the surface charge of the fiber from positive to negative, thereby forming an electrostatically repulsive and stable blend system.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: a smart gel bead with anthocyanins encapsulated in a soybean protein fiber / sodium alginate dual network, wherein the first network matrix is a nano-soybean protein fiber with a cross-beta-fold structure, and the second network backbone is a three-dimensional gel network formed by calcium ion cross-linking of sodium alginate. The soybean protein fiber network and the sodium alginate network interpenetrate each other to form a dual network structure; anthocyanin molecules are encapsulated in the hydrophobic region inside the soybean protein fiber.
[0007] Preferably, the sodium alginate concentration is 10 g / L; the anthocyanin concentration is 0.01-0.1 g / L; the soybean protein fiber is formed by acid-heat induced self-assembly of natural soybean protein and has a cross-beta-sheet structure; the anthocyanin molecules are captured and embedded in the hydrophobic region inside the soybean protein fiber through hydrophobic interactions; the gel beads exhibit a clear color change from pink to blue-purple in the pH range of 2.0-8.0.
[0008] The present invention also provides a method for preparing the above-mentioned smart gel beads, comprising the following steps: (1) Disperse natural soybean protein in deionized water, adjust the pH to 2.0, and heat at 85-95℃ for 12-24 h to allow the protein molecules to self-assemble into nano-soybean protein fibers with a cross-beta-sheet structure; (2) Adjust the pH of the soybean protein fiber dispersion obtained in step (1) to 7.0 to obtain neutral soybean protein fibers with a width of 5-20 nm and a length of 1-30 μm; (3) Mix the neutral soybean protein fiber dispersion obtained in step (2) with anthocyanins, with an anthocyanin addition amount of 0.01-0.15. g / L, stir evenly, and anthocyanin molecules enter the hydrophobic region inside the soybean protein fiber through hydrophobic interaction to prepare protein fiber-anthocyanin composite solution; (4) add protein fiber-anthocyanin composite solution to sodium alginate solution (5-15 g / L), stir evenly to obtain composite bead premix solution; (5) add the composite bead premix solution obtained in step (4) into a certain concentration of Ca²⁺ solution (concentration 0.05-0.2 mol / L, preferably 0.1 mol / L) by peristaltic pump, crosslink for 10-60 min, so that sodium alginate forms a second network gel skeleton, which together with the first network matrix of soybean protein fiber constitutes a double network interpenetrating structure, and finally obtains pH-indicating smart gel beads.
[0009] The peristaltic pump has a drip rate of 1-5 mL / min and a drip height of 0.5-2 cm.
[0010] The resulting gel beads have a diameter of 2-4 mm.
[0011] Compared with the prior art, the present invention has the following advantages:
[0012] (1) This invention utilizes the hydrophobic regions within the cross-beta-sheet structure of soybean protein fibers as embedding sites for anthocyanins, encapsulating cyanidin-3-glucoside molecules within them. This embedding effect isolates anthocyanins from light, heat, and oxygen at the molecular scale, significantly inhibiting anthocyanin degradation. Unlike existing technologies where anthocyanins are simply dispersed in a gel matrix, this invention achieves dual protection of anthocyanins through spatial embedding and hydrophobic stability via a soybean protein fiber network.
[0013] (2) Anthocyanin molecules are confined within the β-folded nanospace of soybean protein fiber, and the conformational freedom of its main component, cyanidin-3-glucoside, is restricted to a certain extent, making its response to changes in H⁺ / OH⁻ concentration more rapid and sensitive. At the same time, the dense hydrogen bond network in the soybean protein fiber matrix provides a microenvironment for proton conduction, further accelerating the structural transformation rate of anthocyanin molecules under different pH conditions.
[0014] (3) The present invention adopts a dual network design with soybean protein fiber as the first network matrix and sodium alginate as the second network skeleton. Soybean protein fiber is uniformly distributed in the sodium alginate gel network as a reinforcing phase. The two form physical cross-linking and hydrogen bond interaction at the molecular scale, which significantly improves the mechanical strength and structural integrity of the gel beads.
[0015] (4) Cyanidin-3-glucoside in anthocyanins has excellent free radical scavenging ability, and soybean protein fiber matrix also has a certain physical barrier effect. The two work together to give the gel beads antioxidant properties, which can effectively delay the oxidation of food lipids and quality deterioration. Attached Figure Description
[0016] Figure 1 These are transmission electron microscope (TEM) images of soybean protein fiber prepared in Example 1 of the present invention, wherein (A) is a TEM image of soybean protein fiber at pH 2.0 and (B) is a TEM image of soybean protein fiber at pH 7.0.
[0017] Figure 2 This is a photograph of the appearance of the smart gel beads prepared in Example 1 of the present invention.
[0018] Figure 3 This is a comparison chart of the hardness of the smart gel beads prepared in Examples 1, 2, 3, 4 and Comparative Example 1 of the present invention. The lowercase letters in the chart indicate the significance of the difference at the P<0.05 level.
[0019] Figure 4The figure shows the encapsulation efficiency of anthocyanins by the smart gel beads prepared in Examples 1, 2, 3, 4 and Comparative Example 1 of this invention. Lowercase letters in the figure indicate significant differences at the P<0.05 level.
[0020] Figure 5 The figure shows the antioxidant properties of the smart gel beads prepared in Examples 1, 2, 3, 4 and Comparative Example 1 of this invention. Uppercase and lowercase letters in the figure indicate the significance of differences at the P<0.05 level.
[0021] Figure 6 The images show the color changes of the smart gel beads prepared in Example 1 of this invention under different pH conditions (pH values of 2.0, 4.0, 6.0, 7.0 and 8.0).
[0022] Figure 7 This is an image showing the application effect of the smart gel beads prepared in Example 1 of the present invention in the visual detection of food freshness. Detailed Implementation
[0023] The technical solution of the present invention will be described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0024] Example 1 (1) Preparation of soybean protein fiber: Soybean protein isolate (SPI) was dispersed in deionized water to prepare a protein solution of 10 g / L. After stirring and hydrating for 12 h, the pH was adjusted to 2.0 with 1 M HCl. The solution was heated in a 90℃ water bath for 12 h with continuous stirring. After heating, it was quickly cooled to room temperature to obtain a nano-soybean protein fiber dispersion with a cross-β-sheet structure; (2) pH adjustment of soybean protein fiber: The pH of the soybean protein fiber dispersion obtained in step (1) was slowly adjusted to 7.0 with 1 M NaOH to obtain neutral soybean protein fibers with a width of 5-20 nm and a length of 1-10 μm. This step ensured that the subsequent sodium alginate composite was carried out under neutral conditions. Since the protein in the acidic fiber dispersion obtained in step (1) is positively charged, it will flocculate instantaneously when directly mixed with the negatively charged sodium alginate, forming an insoluble complex that cannot be formed into regular gel beads in the subsequent calcium ion crosslinking. Therefore, the pH of the fiber dispersion must be adjusted to neutral to reverse the surface charge of the fiber and form a stable blend system with sodium alginate. (3) Preparation of protein fiber-anthocyanin composite solution: The neutral soybean protein fiber dispersion obtained in step (2) is mixed with purple cabbage anthocyanin. The amount of purple cabbage anthocyanin added is 0.1 g / L. The mixture is stirred evenly under light-proof conditions. The anthocyanin molecules enter the hydrophobic region inside the soybean protein fiber through hydrophobic interaction to obtain the protein fiber-anthocyanin composite solution. (4) Preparation of gel bead premix: Sodium alginate powder is dissolved in deionized water to prepare a 10 g / L sodium alginate solution. The protein fiber-anthocyanin composite solution obtained in step (3) is mixed with the sodium alginate solution at a ratio of 7:3 (v / v) and stirred evenly to obtain the composite gel bead premix. (5) Forming of gel beads and construction of double network: The mixed solution obtained in step (4) is transferred to the sampler of the peristaltic pump and dripped into a 0.1 mol / L calcium chloride solution at a dripping speed of 2 mL / min and a dripping height of 1 cm. The mixture is cross-linked and cured for 30 minutes. In a process involving calcium ion cross-linking, sodium alginate forms a second network gel backbone, which, together with the first network matrix of soybean protein fiber, constitutes a double-network interpenetrating structure. The resulting gel beads are collected and repeatedly washed with deionized water to obtain intelligent gel beads containing anthocyanins encapsulated in a soybean protein fiber / sodium alginate double network. The prepared gel beads are uniformly spherical, with a diameter of 3-4 mm, and a uniform color, exhibiting a purple hue at pH 7.0.
[0025] Example 2 The difference between this embodiment and Example 1 is that the heating time in step (1) is 24 h; the amount of anthocyanin added in step (3) is 0.15 g / L; and the volume ratio of protein fiber-anthocyanin composite solution to sodium alginate solution in step (4) is 6:4. The remaining operations are the same as in Example 1. The neutral soybean protein fiber obtained in Example 2 has a width of 5-20 nm and a length of 2-30 μm, which is longer than that of the neutral soybean protein fiber in Example 1. The anthocyanin encapsulation rate of Example 2 was tested to be 87%, which is significantly higher than that of Example 1 (80.14%), Example 3 (75.98%), Example 4 (80.09%) and Comparative Example 1 (70.05%).
[0026] Example 3 The difference between this embodiment and Example 1 is as follows: the amount of anthocyanin added in step (3) is 0.05 g / L; the volume ratio of protein fiber-anthocyanin composite solution to sodium alginate solution in step (4) is 5:5; the concentration of calcium chloride solution in step (5) is 0.15 mol / L, the cross-linking time is 45 min, and the peristaltic pump dripping speed is 4 mL / min. The remaining operations are the same as in Example 1. The hardness of Example 3 was tested to be 863.64 g, which is significantly higher than that of Example 1 (750.84 g), Example 2 (768.8 g), Example 4 (754.68 g), and Comparative Example 1 (758.82 g).
[0027] Example 4 The difference between this embodiment and Example 1 is that the anthocyanin used in step (4) is blueberry anthocyanin (in Example 1 it was purple cabbage anthocyanin), and the rest of the operation is the same as in Example 1. The color saturation of the resulting gel beads under different pH conditions is slightly lower than that in Example 1.
[0028] Comparative Example 1 The difference between this embodiment and Example 1 is that: an equal amount of anthocyanins were directly dispersed in a sodium alginate solution without soybean protein fiber encapsulation, and gel beads were prepared by adding a Ca²⁺ solution of the same concentration. The resulting gel beads exhibited a significantly accelerated degradation rate, decreased color response sensitivity, and shortened indicator lifespan when exposed to light, heat, and oxygen.
[0029] Experiment 2 The smart gel beads prepared in Examples 1, 2, 3, 4, and Comparative Example 1 were used, and their hardness was measured using a texture analyzer. The triggering force and extrusion depth were set to 5 g and 10 mm, respectively, and the speed was 1.0 mm / s. The compression ratio of the hydrogel beads was 40%. The maximum penetration force, expressed as hardness (g), is the force required to rupture the gel bead. The results are as follows: Figure 3 As shown, the increased proportion of sodium alginate in the composite system resulted in Example 3 having the highest hardness value.
[0030] Experiment 3 The smart gel bead samples prepared in Examples 1, 2, 3, 4, and Comparative Example 1 were added to 1 mL of ethanol and centrifuged at 4000 g for 5 minutes. The supernatant was filtered through a 0.45 μm filter membrane to determine the surface anthocyanin content. Finally, the encapsulation efficiency of anthocyanins was calculated using the following formula: Where A1 represents the total anthocyanin content and A0 represents the surface anthocyanin content.
[0031] The results are as follows Figure 4 As shown, all groups had a high anthocyanin encapsulation rate, and the smart gel beads prepared in Example 2 had a better anthocyanin encapsulation rate due to their longer soybean protein fiber length and higher fiber network density.
[0032] Experiment 4 The hydrogel beads prepared in Example 1 were placed in buffer solutions with pH values of 2.0, 4.0, 6.0, 7.0, and 8.0, respectively, and the color changes were observed after standing for 10 minutes. The results showed that the composite hydrogel beads were light pink at pH 2.0; pink at pH 4.0; purplish-red at pH 6.0; purple at pH 7.0; and bluish-purple at pH 8.0. The color changes were clearly distinguishable.
[0033] Experiment 5 The antioxidant activity of the hydrogel beads was evaluated using the ABTS and DPPH free radical scavenging methods. The hydrogel bead samples prepared in Examples 1, 2, 3, 4, and Comparative Example 1 were added to ABTS working solution, which was a mixture of equal volumes of 7 mmol / L ABTS solution and 2.45 mmol / L potassium persulfate solution. After standing at room temperature in the dark for 12–16 h, the solution was diluted with phosphate buffer (pH 7.4) to a absorbance of 0.70 ± 0.02 at 734 nm. After reacting at room temperature in the dark for 10 min, the absorbance was measured at 734 nm. The ABTS free radical scavenging rate of the gel beads was: Where A0 represents the absorbance of ABTS solution with an equal volume of deionized water as the sample, and A1 represents the absorbance of ABTS solution with the sample added. The DPPH test method is as follows: Hydrogel bead samples prepared in Examples 1, 2, 3, 4, and Comparative Example 1 were added to a 0.1 mmol / L DPPH methanol solution and reacted at room temperature in the dark for 30 minutes. The absorbance was measured at 515 nm. The DPPH free radical scavenging rate of the gel beads was: Where A0 represents the absorbance of the DPPH solution with an equal volume of methanol as the sample, and A1 represents the absorbance of the DPPH solution with the sample added.
[0034] like Figure 5 As shown, the ABTS⁺ scavenging rate of each embodiment and Comparative Example 1 was higher than that of DPPH, indicating that the gel beads had different scavenging abilities against two different types of free radicals. Example 2 showed the highest ABTS⁺ and DPPH scavenging rates, reaching 78% and 71.84% respectively, significantly better than the other embodiments and comparative examples. Example 1 showed the second highest antioxidant activity, with ABTS and DPPH scavenging rates of 72.9% and 69.14% respectively, significantly higher than Comparative Example 1 (ABTS 63.56%, DPPH 58.68%). Example 4 showed ABTS and DPPH scavenging rates of 69.64% and 63.2% respectively, lower than Example 1, indicating that the type of anthocyanin has a certain influence on the antioxidant activity of the gel beads. Example 3 showed significantly lower ABTS and DPPH scavenging rates than the other embodiments and Comparative Example 1, possibly due to its lower anthocyanin content (0.05 g / L) and reduced protein fiber ratio leading to fewer hydrophobic binding sites. Additionally, the excessively rapid cross-linking rate may have affected the sufficient migration and binding of anthocyanins into the fiber interior.
[0035] Experiment Six Freshly prepared hydrogel beads from Example 1 were placed together with a blank control group (shrimp without hydrogel beads) at 4°C for storage. The color changes of the hydrogel beads and spoilage indicators of the shrimp (pH value, volatile basic nitrogen (TVB-N) content) were observed periodically. The results showed that the hydrogel beads in fresh shrimp (stored for 0-10 h) were pink to purplish-red; after 32-60 h of storage, the pH increased due to protein decomposition and the production of amines, and the hydrogel beads gradually turned purple; after 60-78 h of storage, a large amount of protein decomposed in the shrimp, and ammonia and histamine gradually accumulated, causing the shrimp to spoil. The generation of a large amount of spoilage products led to a significant increase in pH, and the hydrogel beads turned bluish-purple. This color change indicated that the food had spoiled and was no longer edible.
[0036] Compared to the control group, the experimental group of shrimp containing hydrogel beads showed significantly lower pH values and TVB-N content at 48 h and 72 h of storage. This is attributed to the sustained-release antioxidant active ingredients from the hydrogel beads, which effectively scavenge free radicals during protein oxidation, interrupting the oxidation chain reaction and thus slowing down protein degradation and the formation of biogenic amines (ammonia, histamine). The color change (from pink to purple) of the experimental group shrimp was delayed by approximately 8–15 h compared to the control group, indicating that the hydrogel beads not only indicate the degree of spoilage but also effectively extend the edible window of the shrimp by delaying the spoilage process at its source through antioxidant effects.
[0037] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A smart gel bead with anthocyanins encapsulated in a soybean protein fiber / sodium alginate dual network, characterized in that, Using soybean protein fiber with a cross-β-sheet structure as the first network matrix, anthocyanin molecules are embedded in the hydrophobic region inside the soybean protein fiber through hydrophobic interactions. A three-dimensional gel network formed by sodium alginate is used as the second network backbone. The soybean protein fiber network and the sodium alginate network interpenetrate each other through intermolecular hydrogen bonds and electrostatic interactions to form a double network interpenetrating structure. Calcium ions significantly enhance the interfacial bonding between the two networks, effectively improving the overall structural strength and hardness of the gel beads.
2. The smart gel bead according to claim 1, characterized in that, The gel beads exhibit a clearly discernible color change from pink to bluish-purple within a pH range of 2.0-8.
0.
3. A method for preparing smart gel beads with anthocyanins encapsulated in soybean protein fiber / sodium alginate dual network as described in claim 1, characterized in that, Includes the following steps: (1) Natural soybean protein was acid-heat induced to self-assemble into nano-soybean protein fibers with a cross-beta-sheet structure; (2) The pH of the soybean protein fiber dispersion obtained in step (1) was adjusted to... 7.0, to obtain a neutral soybean protein fiber dispersion; (3) mix the neutral soybean protein fiber dispersion obtained in step (2) with anthocyanin solution to prepare a protein fiber-anthocyanin composite solution; (4) add the protein fiber-anthocyanin composite solution to sodium alginate solution and stir evenly to obtain a composite bead premix; (5) drip the composite bead premix obtained in step (4) into a Ca²⁺ solution of a certain concentration through a peristaltic pump to crosslink and form an interpenetrating double network smart indicator gel bead with sodium alginate as the second network gel skeleton and soybean protein fiber as the first gel network skeleton.
4. The preparation method according to claim 3, characterized in that, The acid-heat induction conditions in step (1) are: pH value of 2.0, temperature of 85-95℃, time of 12-24 h, and the width of the soybean protein fiber is 5-10 nm and the length is 1-10 μm.
5. The preparation method according to claim 3, characterized in that, The concentration of the sodium alginate solution in step (3) is 5-15 g / L.
6. The preparation method according to claim 3, characterized in that, The calcium chloride solution of a certain concentration mentioned in step (5) has a concentration of 0.05-0.2 mol / L, a cross-linking time of 10-60 min, and is dripped using a peristaltic pump with a dripping speed of 1-5 mL / min and a dripping height of 0.5-2 cm.
7. The preparation method according to claim 3, characterized in that, The anthocyanin mentioned in step (4) is at least one of black radish anthocyanin, grape skin anthocyanin or purple cabbage anthocyanin, and its addition amount is 0.01-0.1 g / L.
8. The application of the smart gel beads according to any one of claims 1 to 3 or the smart gel beads prepared by the preparation method according to any one of claims 4 to 7 in smart food packaging.
9. The application according to claim 8, characterized in that, The color of the gel beads changes in a gradient from purplish-red to purple and then to bluish-purple as the pH value of the environment increases. Specifically, for livestock and poultry meat, purplish-red gel beads indicate freshness, purple indicates decreased freshness, and bluish-purple indicates spoilage. For fish, pink to purplish-red gel beads indicate freshness, purple indicates decreased freshness, and bluish-purple indicates spoilage. For shrimp, pink to purplish-red gel beads indicate freshness, purple indicates decreased freshness, and bluish-purple indicates spoilage.
10. The application according to claim 8, characterized in that, The food in question is meat or aquatic products.